Factors affecting the audit quality of pandemic era public accountants - Budiandru Budiandru (AKUNTABEL, 2021)
Audit quality is how likely the auditor finds errors in the company's financial statements to be reported. Good audit quality will make customers give a solid trust to become an added value for auditors. The purpose of this study is to analyze the effect of due professional care, accountability, and reputation of public accounting firms on audit quality during a pandemic. Data were collected using a questionnaire and processed using multiple linear regression with a sample of auditors and students who have worked in public accounting firms in Jakarta. The processing results show that due professional care, accountability, and office reputation significantly affect audit quality during a pandemic. The accounting firm can maintain and improve audit quality by providing education and training to auditors and providing incentives according to performance achievements.